Effect of Quercetin loaded Silver nanoparticles on Gram negative and Gram positive bacteria (Indian Journal of Experimental Biology (IJEB), 2021)
Microorganisms are increasingly becoming resistant to multiple antibiotics and search for effective antibacterial agents continue to challenge researchers in the respective domain. Silver nanoparticles (AgNPs) with physicochemical properties different from their bulk counterparts and show better cellular penetration resulting in higher antimicrobial activity. Here, we studied the antimicrobial activity of AgNPs in pure state as well as when coated with quercetin, and also the mechanism of action. Quercetin is known for its antimicrobial activity, hence applied here for coating it on AgNPs. Spherical AgNPs of size ranging between 10 and 28 nm were synthesised using chemical reduction method. The AgNPs show promising antimicrobial activity in Gram negative bacteria Escherchia coli; however, AgNPs loaded with quercetin did not enhance the antimicrobial activity of AgNPs. The mechanism of antimicrobial activity of AgNPs unravelled in this study was inhibition of bacterial catalase and decrease in membrane potential (MMP) of the bacterial cell with increase in concentration of AgNPs. Another mechanistic aspect was production of reactive oxygen species (ROS) by AgNPs resulting in apoptosis. However, there was no degradation of cellular DNA which suggests that it does not contribute to antibacterial activity of AgNPs.